Antimicrobial Mechanisms and Effectiveness of Graphene and Graphene-Functionalized Biomaterials. A Scope Review - Mohammed, Hiba; Kumar, Ajay; Bekyarova, Elena; Al-Hadeethi, Yas; Zhang, Xixiang; Chen, Mingguang; Ansari, Mohammad Shahnawaze; Cochis, Andrea; Rimondini, Lia (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial infections represent nowadays the major reason of biomaterials implant failure, however, most of the available implantable materials do not hold antimicrobial properties, thus requiring antibiotic therapy once the infection occurs. The fast raising of antibiotic-resistant pathogens is making this approach as not more effective, leading to the only solution of device removal and causing devastating consequences for patients. Accordingly, there is a large research about alternative strategies based on the employment of materials holding intrinsic antibacterial properties in order to prevent infections. Between these new strategies, new technologies involving the use of carbon-based materials such as carbon nanotubes, fullerene, graphene and diamond-like carbon shown very promising results. In particular, graphene- and graphene-derived materials (GMs) demonstrated a broad range antibacterial activity toward bacteria, fungi and viruses. These antibacterial activities are attributed mainly to the direct physicochemical interaction between GMs and bacteria that cause a deadly deterioration of cellular components, principally proteins, lipids, and nucleic acids. In fact, GMs hold a high affinity to the membrane proteoglycans where they accumulate leading to membrane damages; similarly, after internalization they can interact with bacteria RNA/DNA hydrogen groups interrupting the replicative stage. Moreover, GMs can indirectly determine bacterial death by activating the inflammatory cascade due to active species generation after entering in the physiological environment. On the opposite, despite these bacteria-targeted activities, GMs have been successfully employed as pro-regenerative materials to favor tissue healing for different tissue engineering purposes. Taken into account these GMs biological properties, this review aims at explaining the antibacterial mechanisms underlying graphene as a promising material applicable in biomedical devices.